Students' mathematical critical thinking skill: An exploration case study when using argumentation-based learning - Ardi Dwi Susandi; Sudirman Sudirman (Journal of Advanced Sciences and Mathematics Education, 2025)
Background: Critical thinking skills are essential in addressing the learning challenges faced by students in the 21st century. To foster these skills effectively, it is necessary to adopt specific instructional approaches that enhance students’ mathematical critical thinking within the classroom setting.Aims: This study aims to investigate students’ critical thinking abilities in mathematics during the implementation of the Argumentation-Based Learning Process (ABLP) in classroom instruction.Methods: A qualitative case study design was employed, involving 30 eighth-grade students from an A-accredited school in Indonesia. Data sources included ABLP-based worksheets, audio recordings of student group discussions, and interview transcripts. The collected data were analyzed using a triangulation strategy to ensure accuracy, and peer reviews were conducted to validate the findings. The analysis focused on identifying indicators of critical thinking skills at each stage of the ABLP model.Results: The results show that students demonstrated various levels of critical thinking throughout the ABLP stages. However, not all students consistently met the predetermined indicators at each stage of the process. Despite these variations, the findings suggest that ABLP can be an effective pedagogical approach to foster students’ critical thinking in mathematics.Conclusion: This study concludes that ABLP offers meaningful opportunities for students to develop critical mathematical thinking and should be considered as a strategy in mathematics instruction.